Digital Based Academic Service Management at SMA N 1 Kutacane, Southeast Aceh Regency - Faizal Luqman; Nasution, Inom; Nurika Khalila Daulay (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Digital transformation has changed the thinking of teachers and education personnel about the need to balance technology-based learning media with digital competencies in providing academic services. Thus, this research makes an important contribution to understanding how the application of digital technology can improve the effectiveness and efficiency of educational services. This study used descriptive qualitative research methodology. The subjects of this study were principals and teachers who were actively involved in the implementation of digital-based academic service management. In this study, data collection techniques were used; 1) Observation; 2) Interview and 3) Documentation Study. In checking the validity of this research using triangulation techniques. Therefore, a qualitative data analysis method is needed. Data reduction, data presentation, and conclusion drawing and analysis are the phases of data analysis that follow data collection. academic service planning process at SMA N 1 Kutacane, one of which is the formation of small teams in each study group. This strategy supports decentralization and task delegation. Organizing academic services at SMA N 1 Kutacane uses a comprehensive approach that focuses on digital literacy. This strategy includes comprehensive planning from infrastructure to policy for the integration of digital transformation, improving school operational efficiency and student learning experience. Teachers who actively learn and implement the knowledge in school activities and learning communities create a better learning environment. At SMA N 1 Kutacane, digitalization of education began in 2015 with the Model application and Quizizz in 2018. Evaluation at SMA N 1 Kutacane showed some significant weaknesses, such as low understanding and use of digital tools by teachers.